Inclusion and autism : neurodiverse autistic first-person accounts - Halder, Santoshi; Goldstein, Tim; Caudel, Dave (Abingdon, Oxon ; New York : Routledge, 2025)
"This book provides a fertile ground for having the collective voices of the autistic people to understand inclusion and the enigma of the autism spectrum from the neurodiverse lens. The book brings forth the first-person account of autistic adults and unravels various facts about autism spectrum disorder. It offers a fresh outlook on autistic adults, reflecting on inclusion, their challenges, and strengths presenting crucial elements for a successful inclusive model and the foundation of a robust and effective support delivery reinforcing the inclusion of autistic people in society. Through a range of neurodiverse voices, the book presents the world their unique perspectives. It offers valuable insights for future directions and strategic effective pathways stressing the need for a neuro-diverse lens and strength-based focus of support for manifestation and nurturance of abilities and strengths of people. Inclusive and incisive in its making, this book would be useful to the departments of Special Education, Psychology and Applied Psychology, Social Work, Sociology, and Public Health. It would also be an invaluable companion to special educators, in-service and prospective teachers, policy makers, parents, professionals from government and non-government departments, and researchers in the field of disability, diversity, and equity from around the world"--
Mapping inclusion through a neurodiverse lens: unraveling the paradoxes and valorising the strengths of the autism spectrum / Santoshi Halder -- The art of my autistic life / David Atkinson -- Autonomy and inclusion / Patrick Dwyer -- Small house and a tall fence: Women on the spectrum and sexual predators / Dana Vilker -- A journey to becoming autism proud / Kendal Nolan -- Determination / Leah Rosenthal -- Neurodiversity refined: The Neuro Cloud embraces all humans / Tim Goldstein -- Accommodations seeking accommodations / Rev. Stephanie E. H. Friant, M.Div. -- Reimagining the working self: The impact of adult autism diagnosis on a career woman / Barrijean Walsh -- All my hats / Dave Caudel.
Keywords: Autistic people; Social integration; Neurodiversity; PSYCHOLOGY / Psychopathology / Autism; EDUCATION / Special Education / Socially Handicapped